2021
DOI: 10.1186/s13039-020-00524-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomic characteristics of murine breast cancer cell line JC

Abstract: Background Breast cancer (BC), one of the most frequent human tumors, is genetically and histologically heterogeneous. Treatment options can be adapted according to BC subtype. Still, research is necessary to characterize BC biology better and to study potential new treatment options. Murine BC-cell lines can be used as model systems in this respect. Results Here for the first time murine BC-cell line JC was cytogenomically characterized as being c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As a numerically variant karyotype with ~95 chromosomes was already reported in 1982 3 , it can be concluded that the MTLC-1 cell line remained relatively stable during the last 40 years, as also reported for other murine cell lines before. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] Like most of these cell lines, MTLC-1 also showed several dicentric chromosomes normally considered to be instable; also, MTLC-1 is one of the few cell lines with a stable neocentric chromosome. 19,22 By the molecular cytogenetic characterization scheme applied here, a detailed characterization of numerical and structural changes of MTLC-1 was performed, which enabled the determination of ploidy-grade, individual chromosome numbers and involved rearrangements.…”
Section: Discussionmentioning
confidence: 96%
“…As a numerically variant karyotype with ~95 chromosomes was already reported in 1982 3 , it can be concluded that the MTLC-1 cell line remained relatively stable during the last 40 years, as also reported for other murine cell lines before. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] Like most of these cell lines, MTLC-1 also showed several dicentric chromosomes normally considered to be instable; also, MTLC-1 is one of the few cell lines with a stable neocentric chromosome. 19,22 By the molecular cytogenetic characterization scheme applied here, a detailed characterization of numerical and structural changes of MTLC-1 was performed, which enabled the determination of ploidy-grade, individual chromosome numbers and involved rearrangements.…”
Section: Discussionmentioning
confidence: 96%
“…The first cytogenomic characterization of the tumor cell line I-10 revealed a slightly hyperdiploid karyotype of 43 chromosomes, with relatively few imbalances and breakpoints for a cell line that is in cell culture for around 55 years. Interestingly, I-10 is a tumor cell line with dicentric chromosomes, which are normally considered to be unstable [5,[13][14][15][16][17][18][19][20][21][22][23][24][25]. It is one of the few cell lines with a stable neocentric chromosome [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Here, a comparison of translated I-10-specific imbalances was performed, similar to that performed for other murine cell lines [5,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Sequencing analyses might also be fruitful in the future, as subtype-specific differences in somatic mutations were found in testicular germ cell tumors [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…JC cells, a murine primary breast cancer cell line characterized as basal-like or luminal B type [ 66 ], was purchased from Bioresource Collection and Research Center (Hsinchu, Taiwan) and cultured in the RPMI-1640 Medium (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 1 mM sodium pyruvate and 4.5 g/L glucose. 4T1 cells, a murine triple-negative breast cancer cell line, was provided from American-Type Culture Collection (Manassas, VA) and maintained in RPMI-1640 Medium.…”
Section: Methodsmentioning
confidence: 99%